Preventing Underage Drinking Using Getting To Outcomes(TM) with the SAMHSA Strategic Prevention Framework to Achieve Results - Imm, Pamela (RAND Corporation, 2007)
Alcohol is the primary contributor to adolescent deaths in the United States. Structured according to the Substance Abuse and Mental Health Services Administration's (SAMHSA's) Strategic Prevention Framework, a five-step prevention approach, this comprehensive guide to developing, implementing, and evaluating a communitywide plan to prevent underage drinking adopts the Getting To Outcomes model of evaluation, accountability, and improvement.